Objective quantification of vitreous haze on optical coherence tomography scans: no evidence for relationship between uveitis and inflammation in multiple sclerosis. (18th August 2019) - Coric, D.; Ometto, G.; Montesano, G.; Keane, P. A.; Balk, L. J.; Uitdehaag, B. M. J.; Petzold, A.; Crabb, D. P.; Denniston, A. K.
Abstract : Background and purpose: The occurrence of intermediate uveitis, which is characterized by the presence of vitreous haze (VH), in patients with multiple sclerosis (MS) may be a sign of coexistent inflammatory central nervous system (CNS) disease activity. Using an automated algorithm to quantify VH on optical coherence tomography (OCT) scans, the aim was to investigate whether VH in MS patients is associated with signs of inflammatory CNS disease activity. Methods: Vitreous haze was quantified on OCT macular volume scans of 290 MS patients and 85 healthy controls (HCs). The relationship between VH and clinical, retinal OCT and magnetic resonance imaging parameters of inflammatory disease activity was investigated using generalized estimating equations. Results: Mean VH scores did not differ between patients and HCs ( P = 0.629). Six patients (2.1%) showed values higher than the highest of the controls by HCs. VH scores did not differ between the different disease types or between eyes with and without a history of optic neuritis ( P = 0.132). VH was not associated with inner nuclear layer volume on OCT ( P = 0.233), cerebral T2 lesion load on magnetic resonance imaging ( P = 0.416) or the development of new relapses ( P = 0.205). Conclusion: In this study, OCT‐based automated VH estimation did not detect increased vitreous inflammation in MS patients compared to HCs and did not find an association with CNS inflammatory burden.